The summer guests [compact disc, unabridged] - Monroe, Mary Alice (Simon & Schuster Audio, Inc., 2019)
Late August is a beautiful time on the Southern coast, the peach trees are ripe, the ocean is warm, and the sweet tea is icy. A perfect time to enjoy the rocking chairs on the porch. But beneath the calm surface bubbles a threat: it's also the beginning of peak hurricane season. When a sudden storm threatens the coasts of Florida and South Carolina, an eclectic group of evacuees flee for the farm of their friends Grace and Charles Phillips in North Carolina: the Phillips's daughter Moira and her rescue dogs, famed equestrian Javier Angel de la Cruz, makeup artist Hannah McLain, horse breeder Gerda Klug and her daughter Elise, and island resident Cara Rutledge. They bring with them only the few treasured possessions they can carry. Strangers to all but the Phillips, they must ride out the storm together.